2018
DOI: 10.14202/vetworld.2018.474-479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiplex polymerase chain reaction as an alternative to conventional antibiotic sensitivity test

Abstract: AimThis study was designed to evaluate the potential of the use of multiplex polymerase chain reaction (PCR) as an alternative to conventional antibiotic sensitivity test.Materials and MethodsIsolates of Staphylococcus aureus (total = 36) from clinical cases presented to Teaching Veterinary Clinical Complex of College of Veterinary and Animal Sciences (CVAS), Navania, Udaipur, were characterized by morphological, cultural, and biochemical methods. Then, the isolates were further subjected to molecular characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…These are time-consuming processes where time can be the difference between lives saved or lives lost. Newer methods to accelerate this process require costly equipment and special expertise [29], [30]. Similarly, there is need to differentiate between dead and live bacteria after processes intended to sterilize lifesaving fluids or surgical equipment [31] including products intended for ingestion [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…These are time-consuming processes where time can be the difference between lives saved or lives lost. Newer methods to accelerate this process require costly equipment and special expertise [29], [30]. Similarly, there is need to differentiate between dead and live bacteria after processes intended to sterilize lifesaving fluids or surgical equipment [31] including products intended for ingestion [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, Al-Saad et al (2016) and 2019 observed the prevention of DNA expression of the Afla R gene after control of mycotoxigenic A. flavus by probiotic preparation, cinnamon, and olive oils. Moreover, Rathore et al (2018) and Zheng et al (2015) detected that there is a strong relation similarity between traditional diffusion tests and gene expression of bacteria such as S. aureus and Enterococcus faecium treated by traditional drugs (58.3%-100). In addition, the hybrid Nanocomposite with benefit molecules of microbial cells resulted in their damage and death (Xiao et al, 2016;Meena et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in order to obtain comprehensive insight into the infection, its pathogens and treatment options, which strictly depend on the specific pathogens identified, techniques should be used that are quick, cost-effective and are also able to identify possible drug resistance. After the extensive genotyping of bacteria in recent years, multiplex PCR has been shown to be effective in identifying even multi-drug-resistant pathogens [130,131]. In laboratories that do not have the facility of the most advanced PCR technology, a combination of semen culture and PCR seems reasonable.…”
Section: Comparison Of Traditional Semen Cultures Versus Microbiologi...mentioning
confidence: 99%